O Promise Me. - Winston, Monica A. (Early American Life, 2003)
Discusses a lawsuit filed by Joseph Pettengill, publisher of the magazine 'Village Transcript,' against Emily Brown for breach of promise. Amount of damages in the lawsuit; Details of the lawsuit; Issues analyzed in the lawsuit; Judgment on the case.